One new species of the genus Sida L. (Malvaceae) for the flora of Vietnam - Xuyen, Do Thi (Academia Journal of Biology, 2014)
Sida parvifolia DC. (Malvaceae) is a new record for the flora of Vietnam. It has some especial characters as prostrate herbs, leaves penninerved, stipules of paid not different, flower axillary solitary, styles and mericarps 5. The specimens were collected in the Truongsa archipelago (Namyet, Songtutay, Truongsalon and Sonca islands), Khanhhoa province.